2017
DOI: 10.1101/108506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insular Cortex Mediates Approach and Avoidance Responses to Social Affective Stimuli

Abstract: Social animals detect the affective states of others and utilize this information to orchestrate appropriate social interactions. Social affective behaviors include cooperation, reproductive acts and avoiding sick individuals. In a social affective behavioral test in which experimental adult male rats were given the choice to interact with either naive or stressed conspecifics, the experimental rats demonstrated both approach and avoidant behaviors towards the conspecific, depending upon the age of the conspec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 117 publications
(130 reference statements)
6
43
0
Order By: Relevance
“…Experimental observer rats were free to interact with either of the targets. Consistent with other observations [8, 9] experimental adult rats avoided stressed conspecifics [31]. Notably, these observations were made in unfamiliar groups of rats.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Experimental observer rats were free to interact with either of the targets. Consistent with other observations [8, 9] experimental adult rats avoided stressed conspecifics [31]. Notably, these observations were made in unfamiliar groups of rats.…”
Section: Introductionsupporting
confidence: 92%
“…As described previously [31], the SAP test allows for the quantification of social exploration of an experimental rat directed toward 2 target conspecifics, 1 naïve to treatment and the other stressed. The SAP test began with 2 days of habituation: experimental rats were acclimated to the test area, a clear plastic cage (50 × 40 × 20cm, L × W × H) with a wire lid, for 60 min and then presented 2 empty restraint chambers (day 1) or 2 naive conspecifics (day 2) housed in the restraint chambers (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insula has been implicated in many studies of depression examining functional connectivity, volumetric analyses and biomarkers for treatment outcomes 32 . The insula is also involved in emotion processing, self-awareness and motor control 33 and also specifically in anticipatory cues and approach and avoidance behavior 34, 35 . As with the precuneus, reduced insula may indicate a biological mechanism whereby reduced activity during avoidance of negative stimuli could increase exposure to negative events and therefore more anhedonic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies further demonstrated roles for the IC in multisensory (Gogolla, Takesian, Feng, Fagiolini, & Hensch, 2014; Rodgers, Benison, Klein, & Barth, 2008) and pain processing (Tan et al, 2017), representation of valence (Wang et al, 2018), learning and memory (Bermúdez-Rattoni, Okuda, Roozendaal, & McGaugh, 2005; Lavi, Jacobson, Rosenblum, & Lüthi, 2018), social interactions (Rogers-Carter et al, 2018), gustation (Peng et al, 2015; Wang et al, 2018), drug cravings and malaise (Contreras, Ceric, & Torrealba, 2007), and aversive states such as hunger, thirst, and anxiety (Gehrlach et al, 2019; Livneh et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%